THE LEGISLATIVE DIGRESSION IN THE FACE OF (NON-) EQUALITY OF WOMEN IN THE EMPLOYMENT RELATIONSHIP (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The present study aims to present, at first, a legislative digression regarding gender equality both in the constitutional text and in other legal norms, guided by a patriarchal, sexist and conservative model of society, which associates the image of women to fragility, as well as reinforces the idea of inferiority and submission to men, home and motherhood. In a second moment, the work starts to demonstrate the legal norms pertaining to the special protection of women in labor relations with its essential elements, such as maternity leave, stability, the existence or not of special breaks for women, intimate searches, request for medical exams. pregnancy, sex discrimination, and the foundations that legitimize these rules, in order to establish, in a third moment, respect for gender equality in labor relations. Finally, the study reveals that there are remnants of patriarchal society, machismo, as well as cultural and educational obstacles that need to be overcome in order to enable a social transformation regarding equal rights between men and women, including in labor relations , since the consequences of inequality interfere in the exercise of citizenship and in the development of the entire Brazilian society. To carry out this research, the methodology used was a literature review, with an approach to content extracted from normative texts, books, articles, journals, all related to the topic.